PENGARUH KEPUASAAN PELANGGAN DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN AIR MINUM DALAM KEMASAN (AMDK) MAS KOTA BENGKULU - Sari, Widi Ratna; Ekowati, Sri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research aims to determine the influence of customer satisfaction and customer trust on the loyalty of bottled drinking water (AMDK) customers in Bengkulu City, both partially and simultaneously. This type of research is a type of quantitative descriptive research. There are several factors that influence customer loyalty, namely customer satisfaction and customer trust. The object of this research is the people of Bengkulu city, totaling 120 people. In this research the author used data collection methods by means of observation, interviews and distributing questionnaires. Data analysis techniques in this research use instrument testing, classical assumption testing, analysis of respondent responses, multiple linear regression analysis, hypothesis testing pand analysis of the coefficient of determination. The research results show that customer satisfaction has a positive effect on customer loyalty, customer trust has a positive effect on customer loyalty. So, from the results of the research that has been carried out, it can be concluded that customer satisfaction and customer trust have a partial and simultaneous effect on customer loyalty in the people of Bengkulu City. Keywords: Customer Satisfaction, Customer Trust, and Customer Loyalty